Duty of disclosure during patent prosecution in India. (June 2015) - Sharma, Sneha; Padmavati, Manchikanti
Abstract: The Indian Patent Office has witnessed an increase in both volume and earnestness from applicants as a result of a duty to disclose that is mandated under Section 8, The Patents Act, 1970. There is a need to delink this with its original purpose. The present study aims at tracing the contours of the duty to disclose requirement in India and in the light of the recent cases, examine the extent to which Section 8 accomplishes the purpose. Elaboration of guidelines for Section 8 in the Manual for Patent Practice and Procedure and need for online linking of databases are suggested as measures for improvement. Highlights: Approaches to Section 8 the Indian Patents Act were analyzed based on patent revocation and opposition cases. Reviewed Committee reports and case law to understand the policy perspective of Section 8 of the Act. Proposed measures for improving compliance for Section 8 and discussed Examiner tools development.